It’s not fair: Folk intuitions about disadvantageous and advantageous inequity aversion - Alex Shaw; Shoham Choshen-Hillel (Judgment and Decision Making, 2017)
People often object to inequity; they react negatively to receiving less than others (disadvantageous inequity aversion), and more than others (advantageous inequity aversion). Here we study people’s folk intuitions about inequity aversion: what do people infer about others’ fairness concerns, when they observe their reactions to disadvantageous or advantageous inequity? We hypothesized that, people would not intuitively regard disadvantageous inequity aversion by itself as being rooted in fairness, but they would regard advantageous inequity aversion by itself as being rooted in fairness. In four studies, we used vignettes describing inequity aversion of a made up alien species to assess people’s folk intuitions about inequity aversion. The studies supported our main hypothesis that disadvantageous inequity aversion, without advantageous inequity aversion, does not fit people’s folk conception of fairness. Instead, participants reported it to be rooted in envy. According to these results, the claim that disadvantageous inequity aversion reveals a concern with fairness, does not readily accord with people’s intuitions. We connect these findings to other pieces of evidence in the literatures of behavioral economics, developmental psychology, and social psychology, indicating that lay people’s intuitions may be on the mark in this case. Specifically, unlike advantageous inequity aversion, disadvantageous inequity aversion need not be rooted in a sense of fairness. % revised abstract